OFDM-Based broadhand wireless networks : - Liu, Hui (John Wiley & Sons, 2005)
OFDM-based Broadband Wireless Networks covers the latest technological advances in digital broadcasting, wireless LAN, and mobile networks to achieve high spectral efficiency, and to meet peak requirements for multimedia traffic. The book emphasizes the OFDM modem, air-interface, medium access-control (MAC), radio link protocols, and radio network planning.